PEMBERITAAN PERTANIAN OLEH SURAT KABAR DAERAH: - STUDI KASUS PADA RUBRIK KANDA RAHARJA SKH. KEDAULATAN RAKYAT - - Ngatif, Muh. Syaiful; Harsoyo, Harsoyo; Subejo, Subejo (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2005)
The Study aims to know and to analyze the comparison between agricultural news and non-agricultural news in term off frequency, space, length, position, topic and coverage area on special rubric of agricultural issues of Kedaulatan Rakyat daily newspaper. Another purpose of the study was to know about editorial policy of the newspaper in reporting agricultural news and information. The research method used in the study was